Damage quantification in Physalis peruviana L. infected by the new putative sobemovirus physalis rugose mosaic virus - Gorayeb E.S.* (2020)
© 2020, Sociedade Brasileira de Fitopatologia.A putative new virus, physalis rugose mosaic virus (PhyRMV), has been reported more frequently in Physalis peruviana associated with severe symptoms. In this study the damage caused by sap-inoculated PhyRMV in P. peruviana was assessed based on the comparison of host vegetative and reproductive parameters between virus-infected and healthy plants. Infected plants confirmed using molecular assays, showed a reduction in growth, leaf area, specific leaf area (SLA) and relative chlorophyll content. PhyRMV-infected plants yielded 70% less fruit of general lower quality parameters, except for pH, compared with the healty plants. Finally, seeds from PhyRMV-infected plants showed a reduced germination rate and, in accelerated aging assay, vigor of seeds were also significantly reduced.